Development and Optimization of Nasal Composition of a Neuroprotective Agent for Use in Neonatology after Prenatal Hypoxia - Igor Belenichev; Olena Aliyeva; Bogdan Burlaka; Kristina Burlaka; Oleh Kuchkovskyi; Dmytro Savchenko; Valentyn Oksenych; Oleksandr Kamyshnyi (MDPI AG, 2024)
The intranasal route of drug administration is characterized by high bioavailability and is considered promising for rapid delivery of drugs with systemic action to the central nervous system (CNS), bypassing the blood-brain barrier. This is particularly important for the use of neuroprotective drugs in the treatment of brain tissue damage in infants caused by the effects of intrauterine hypoxia. The creation of new dosage forms for neonatology using mathematical technologies and special software in pharmaceutical development allows for the creation of cerebroprotective drugs with controlled pharmaco-technological properties, thus reducing time and resources for necessary research. We developed a new nasal gel formulation with Angiolin using a Box-Behnken experiment design for the therapy of prenatal CNS damage. It was found that the consistency characteristics of the nasal gel were significantly influenced by the gelling agent and mucoadhesive component-sodium salt of carboxymethylcellulose. We optimized the composition of nasal gel formulation with Angiolin using the formed models and relationships between the factors. The optimized nasal gel composition demonstrated satisfactory thixotropic properties. The 1% gel for neuroprotection with Angiolin, developed for intranasal administration, meets all safety requirements for this group of drug forms, showing low toxicity and no local irritant or allergic effects.